2010
DOI: 10.1186/1471-2334-10-116
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for significant liver fibrosis among HIV-monoinfected patients

Abstract: BackgroundHIV-monoinfected patients may be at risk for significant liver fibrosis, but its prevalence and determinants in these patients are unknown. Since HIV-monoinfected patients do not routinely undergo liver biopsy, we evaluated the prevalence and risk factors of significant hepatic fibrosis in this group using the aspartate aminotransferase (AST)-to-platelet ratio index (APRI).MethodsWe conducted a cross-sectional study among HIV-infected patients negative for hepatitis B surface antigen and hepatitis C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
67
3
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 30 publications
19
67
3
3
Order By: Relevance
“…Our findings were generally consistent with those from other studies[23, 25, 29]. In their evaluation of FIB-4 markers in HIV mono-infected women, the associations of low CD4 count, detectable viral load and ART use in the study of Blackard, et al were consistent with our findings[23].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings were generally consistent with those from other studies[23, 25, 29]. In their evaluation of FIB-4 markers in HIV mono-infected women, the associations of low CD4 count, detectable viral load and ART use in the study of Blackard, et al were consistent with our findings[23].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the lack of APRI elevation risk associated with ARV treatment duration or specific ARV classes and agents affirms findings in studies of HIV mono-infected adults that chronic ARV treatment does not increase the risk of elevated APRI [810]. The 0.8% prevalence of APRI > 1.5 in this pediatric cohort appears lower than rates of 3.0–3.9% reported in several studies of HIV-infected adults [79] and much lower than the 8% rate observed in one adult study [10]. This lower prevalence among HIV-infected children is likely attributable to lower rates in HIV-infected children compared to HIV-infected adults of other factors that contribute to liver problems, such as viral hepatitis and alcohol use (only 36% of perinatal HIV AMP participants reported alcohol use [11]).…”
Section: Discussionsupporting
confidence: 59%
“…The small magnitude of the risk of APRI elevation is largely reassuring about the status of liver health in perinatally HIV-infected children but this optimistic interpretation is tempered by the relatively low sensitivity of these APRI cut-offs for detecting liver fibrosis in children [6]. In addition, the lack of APRI elevation risk associated with ARV treatment duration or specific ARV classes and agents affirms findings in studies of HIV mono-infected adults that chronic ARV treatment does not increase the risk of elevated APRI [810]. The 0.8% prevalence of APRI > 1.5 in this pediatric cohort appears lower than rates of 3.0–3.9% reported in several studies of HIV-infected adults [79] and much lower than the 8% rate observed in one adult study [10].…”
Section: Discussionmentioning
confidence: 98%
“…25 were found in 37 (59.7%) and 5 (8%) patients, respectively [22]. Conversely, a slightly higher prevalence of 8% of APRI values >1.5 was found in 432 HIV-mono-infected patients, and both diabetes and detectable HIV viremia were confirmed as risk factors for significant fibrosis [30]. However, the presence of obesity in 50% of the cohort could have contributed to the higher prevalence of significant fibrosis.…”
Section: Discussionmentioning
confidence: 85%